1994
DOI: 10.1126/science.8128244
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feedback Defining a Circadian Clock: Autoregulation of the Clock Gene frequency

Abstract: The frequency (frq) locus of Neurospora crassa was originally identified in searches for loci encoding components of the circadian clock. The frq gene is now shown to encode a central component in a molecular feedback loop in which the product of frq negatively regulated its own transcript, which resulted in a daily oscillation in the amount of frq transcript. Rhythmic messenger RNA expression was essential for overt rhythmicity in the organism and no amount of constitutive expression rescued normal rhythmicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
610
2
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 577 publications
(639 citation statements)
references
References 43 publications
24
610
2
1
Order By: Relevance
“…Genetic studies, initially carried out in the fruit fly Drosophila (Hardin et al 1990) and the fungus Neurospora (Aronson et al 1994), and later extended to mammals, showed that circadian oscillations are generated at the molecular level. The core molecular mechanism of these oscillations relies on the negative autoregulatory feedback exerted by clock proteins on the expression of their genes (Dunlap 1999;Young & Kay 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies, initially carried out in the fruit fly Drosophila (Hardin et al 1990) and the fungus Neurospora (Aronson et al 1994), and later extended to mammals, showed that circadian oscillations are generated at the molecular level. The core molecular mechanism of these oscillations relies on the negative autoregulatory feedback exerted by clock proteins on the expression of their genes (Dunlap 1999;Young & Kay 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the dark, a heterodimeric WCC (D-WCC) binds to the C-box (the distal LRE) of the frq promoter, activating its transcription (Crosthwaite et al 1997;Cheng et al 2001b;Froehlich et al 2003;Dunlap and Loros 2004). On the other hand, FRQ and FRH (FRQinteraction RNA helicase), the negative elements in the loop, repress the transcription of frq by inhibiting WCC activity (Aronson et al 1994;Cheng et al 2001aCheng et al , 2005Denault et al 2001). The WC phosphorylation in the dark appears to be an important event in this process.…”
mentioning
confidence: 99%
“…In Neurospora the circadian pacemaker is closely related to the expression of the frequency (frq) gene into its protein (FRQ), which is regulated by a negative feedback, i.e., expressed FRQ protein inhibits its own transcription [2,5]. In a 3-dimensional representation of the model (Fig.…”
Section: Local Curve Optimization For Temperature Compensationmentioning
confidence: 99%